Collaborative leadership dynamics - AlReshaid, Faisal (2025)
Purpose: Engaging a former dual Chief Executive Officer (CEO)-chair as the chairperson while appointing a new CEO retains the expertise of the incumbent and minimizes disruptions during leadership transitions. Although existing research has examined various aspects of the division of CEO and chair roles,such as power dynamics, succession patterns and leadership during crises, there are still significant gaps in understanding how organizations can effectively harness the collaborative potential of two leaders while refining their distinct roles. Design/methodology/approach.This study leverages qualitative data from an emerging market context where the statutory separation of chair and CEO roles has been implemented. This study pursued 22 semi-structured interviews in total with chair, CEO and top managers. Findings. The findings reveal that successful role separation requires deliberate and ongoing co-creation and negotiation of the chair and CEO roles, with mutual adaptation crucial to navigating power dynamics and relational tensions. Additionally, the effectiveness of the transition significantly hinges on clear role boundaries and proactive relational management among top executives. Originality/value. We explore how the individual who previously held the dual role collaborates with the successor in one of the newly separated top positions. Additionally, we examine the broader implications for organizational functioning, offering strategic insights for organizations globally as they adapt to the growing trend of separating top executive roles in leadership and governance.